Scalarization method in problems of elastic surface-wave propagation in rotating transversely isotropic half-space - Igor P. Miroshnichenko; Vadim A. Pogorelov; Valery P Sizov (Advanced Engineering Research, 2015)
The work objectives are to generalize the scalarization method of dynamic elastic fields in the transversely isotropic media to the tasks for the environments rotating with a constant angular velocity, and to develop the methodological apparatus for describing the effect of rotation on the parameters of surface acoustic waves. On the basis of this method, the scientific-methodical device for the construction of new acoustic-wave gyroscopes is proposed. Parameter determination ratios for surface-acoustic waves (SAW) propagating on the boundary of the rotating half-space of the transversely isotropic material with arbitrarily spaced axis of material symmetry are obtained and validated. An example of the numerical simulation for the isotropic rotating half-space case is given. The proposed methodological apparatus and numerical simulation examples can be used to develop new types of gyroscopes on acoustic-wave systems for navigation, guidance and control of various mobile objects in aviation, robotics, etc